2004
DOI: 10.1017/s0950268803001080
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and prognosis of bacteraemia in Italy

Abstract: A prospective multi-centre study was conducted to assess the microbiological pattern and prognostic factors of bacteraemia and their impact on clinical outcome. All patients admitted to 41 Italian hospitals over 2 months, from whom one or more clinically significant organisms were isolated from blood culture, were studied according to a standardized protocol and case definition. A total of 156 episodes of bacteraemia were identified in 20,601 patients. There were 3.9 episodes of nosocomially acquired bacteraem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…3,4 Several studies have retrospectively reported incidence, epidemiology and risk factors for acquisition and outcome of bloodstream infection (BSI). 2,[5][6][7][8][9][10] However, few studies have examined a wide range of thematic areas prospectively as prognostic factors for patient outcome. 9,10 Identifying modifiable factors can assist in minimizing the adverse outcome of nosocomial bacteraemia.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Several studies have retrospectively reported incidence, epidemiology and risk factors for acquisition and outcome of bloodstream infection (BSI). 2,[5][6][7][8][9][10] However, few studies have examined a wide range of thematic areas prospectively as prognostic factors for patient outcome. 9,10 Identifying modifiable factors can assist in minimizing the adverse outcome of nosocomial bacteraemia.…”
Section: Introductionmentioning
confidence: 99%
“…B acteremia is an important public health concern, with a reported rate of 7.6 to 16.9 per 1,000 hospital admissions in many countries and 30-day mortality greater than 20%. [1][2][3] The incidence increases markedly with age, and bacteremia is associated not only with greater short-term mortality, but also with long-term impairment of health and high risk of death. 4,5 As average life expectancy increases in most countries, bacteremia may become an even more common clinical problem.…”
mentioning
confidence: 99%
“…Age is a strong predictor of mortality in patients with bacteremia, but the association between age and mortality is not clear. Former studies have shown a relative risk of death within 30 days ranging from 1.9 to 6.5 in patients aged 65 and older compared with younger patients, 2,6,7 but those studies were clinic based and investigated the effect of age in subpopulations such as patients in the intensive care unit or with cancer, 3,8 patients in geriatric hospitals, 9 and patients with infection caused by selected bacterial species. 7,10 The results may therefore have limited generalizability and are potentially biased because of incomplete follow-up, 9,11,12 lack of control groups, 9,[12][13][14] and uncontrolled confounding from diseases other than bacteremia.…”
mentioning
confidence: 99%
“…1 Bacteremia is related to the presence of viable bacteria in the blood confirmed by cultures in which contamination has been effectively ruled out. 4,5 This may or may not have any clinical significance because harmless, transient bacteremia may occur following dental work or other minor medical procedures; however, it is generally clinically benign and self-resolving in people who do not have an underlying illness or immune deficiency or a turbulent cardiac blood flow.…”
Section: Introductionmentioning
confidence: 99%